A Paradigm shift in China: Globalisation Impact on Guanxi - Zhang, Jian (2003)
The Single-embedded case with multi-subunits Study is a qualitative research approach that the researcher designed to gain an in-depth knowledge of a cultural phenomenon that had been booming researched: guanxi. It combines several approaches to case study research, borrowing from the positivist tradition, the interpretative approach and the qualitative research corpus. It involves the observation and analysis of several sub-sites using namely theoretical propositions comparisons and pattern matching techniques to analyse data. This dissertation primarily explains the globalisation impact on the unique Chinese culture concept of guanxi that led to an emerging conceptualized model of guanxi in current business society in China, followed by an illustration and discussion of how and why international marketers should cope with the paradigm shift of culture. The results obtained and finally, a note of reflection on the entire experience.